Model development for the design of control strategies of the primary drying of lyophilization in vials. Issue 15 (15th November 2022) - Chia, Andrea; Bouchard, Jocelyn; Poulin, Éric; Lapointe-Garant, Pierre-Philippe
Abstract: This paper proposes a development to reformulate the fundamental equations of primary drying into a linear-based representation to support control design. The model is expressed by transfer functions with variable gains that incorporate analytical relations derived from a phenomenological model. The time constants denote the dynamics of the heating/cooling and vacuum systems. Compared to fundamental equations, this approach simplifies the development and implementation of well-established control algorithms. The quality of the proposed representation is illustrated in the design of a control system using two different strategies: model predictive control and a feedback controller with proportional-integral action. The simulation case study allows assessing the performance of both designs with regard to cycle time reduction and robustness under parametric disturbances. Results evidence that the proposed model is detailed enough to provide accuracy in a simplified way, facilitating the implementation of in-line control strategies, which in turn enable significant reductions of drying time.